Osteoid-Osteoma of the Ilium Associated with Malignant Hypertension in an Adult Female - KC , Bikash; Lakhey , RB; Shah , LL; Pokharel , RK (Journal of Institute of Medicine Nepal, 2014)
Osteoid-osteoma, a benign bone tumor, is rare in the ilium bone. Its incidence is uncommon after third decades of life, and can represent a significant diagnostic challenge, resulting in a delay of treatment. We present a 38 years old lady who presented with history of severe right gluteal pam, more during night, and was relieved with non-steroidal anti-inflammatory drugs. Malignant hypertension was associated co-morbid condition without any underlying cause. Plain radiograph was initially normal and her diagnosis was delayed for more than six months until computed tomography (CT) scans and magnetic resonance imaging (MRI) showed a circumscribed lesion of the right ilium suggestive of Osteiod Osteoma. Minimally invasive flouroscopy guided curettage was done, and histopathological findings confirmed the diagnosis of osteoid-osteoma, After surgery, the pain was significantly relieved and, surprisingly, the hypertension was controlled, and she was discharged on single antihypertensive drug in maintenance dose